International Debt Statistics 2017 - World Bank (Washington, DC: World Bank, 2016)
The World Bank's annual report on the external debt of developing countries includes comprehensive data for 125 developing countries, as well as summary data for regions and income groups. This year’s edition of International Debt Statistics is designed to respond to user demand for timely, comprehensive data on trends in external debt in developing countries. As in previous years, IDS provides statistical tables showing the external debt of developing countries that report public and publicly guaranteed external debt to the World Bank’s Debtor Reporting System (DRS). In addition, the publication showcases the broader spectrum of debt data collected and compiled by the World Bank. These include the high frequency, quarterly data for high-income economies and select developing countries reporting to the joint World Bank–IMF Quarterly External Debt Statistics (QEDS) and the Public Sector Debt Statistics (PSDS) database. Presentation and access to data have been rendered to improve the user experience.